Numb is not a critical regulator of Notch-mediated cell fate decisions in the developing chick inner ear - Eddison, Mark; Weber, Sara J.; Ariza-McNaughton, Linda; Lewis, Julian; Daudet, Nicolas (Frontiers in Cellular Neuroscience, 2015)
The Notch signaling pathway controls differentiation of hair cells and supporting cells in the vertebrate inner ear. Here, we have investigated whether Numb, a known regulator of Notch activity in Drosophila, is involved in this process in the embryonic chick. The chicken homolog of Numb is expressed throughout the otocyst at early stages of development and is concentrated at the basal pole of the cells. It is asymmetrically allocated at some cell divisions, as in Drosophila, suggesting that it could act as a determinant inherited by one of the two daughter cells and favoring adoption of a hair-cell fate. To test the implication of Numb in hair cell fate decisions and the regulation of Notch signaling, we used different methods to overexpress Numb at different stages of inner ear development. We found that sustained or late Numb overexpression does not promote hair cell differentiation, and Numb does not prevent the reception of Notch signaling. Surprisingly, none of the Numb-overexpressing cells differentiated into hair cells, suggesting that high levels of Numb protein could interfere with intracellular processes essential for hair cell survival. However, when Numb was overexpressed early and more transiently during ear development, no effect on hair cell formation was seen. These results suggest that in the inner ear at least, Numb does not significantly repress Notch activity and that its asymmetric distribution in dividing precursor cells does not govern the choice between hair cell and supporting cell fates.